New insights into the systematics of Malagasy mongoose‐like carnivorans (Carnivora, Eupleridae, Galidiinae) based on mitochondrial and nuclear DNA sequences. (21st May 2017) - Veron, Géraldine; Dupré, Délia; Jennings, Andrew P.; Gardner, Charlie J.; Hassanin, Alexandre; Goodman, Steven M.
Abstract: The Malagasy carnivorans (Eupleridae) comprise seven genera and up to ten species, depending on the authority, and, within the past decades, two new taxa have been described. The family is divided into two subfamilies, the Galidiinae, mongoose‐like animals, and the Euplerinae, with diverse body forms. To verify the taxonomic status of Galidiinae species, including recently described taxa, as well as some recognized subspecies, we studied intrageneric genetic variation and structure, using both mitochondrial and nuclear markers. Our results suggest the recognition of four species in the Galidiinae, rendering each genus monospecific. We propose to recognize three subspecies in Galidia elegans ( G. e. dambrensis, G. e. elegans, and G. e. occidentalis ), two subspecies in Mungotictis decemlineata ( M. d. decemlineata and M. d. lineata ), and two subspecies in Galidictis fasciata ( G. f. fasciata and G. f. grandidieri, the latter was recently described as a distinct species). Our results indicate also that Salanoia durrelli should be treated as a junior synonym of Salanoia concolor . Low levels of intraspecific divergence revealed some geographical structure for the Galidiinae taxa, suggesting that environmental barriers have isolated certain populations in recent geological time. All taxa, whether at the species or subspecies level, need urgent conservation attention, particularly those with limited geographical distributions, as all are threatened by forest habitat degradation. Abstract : New insights into the systematics of Malagasy mongoose‐like carnivorans (Carnivora, Eupleridae, Galidiinae) based on mitochondrial and nuclear DNA sequences. Géraldine Veron, Délia Dupré, Andrew P. Jennings, Charlie J. Gardner, Alexandre Hassanin, Steven M. Goodman. This is the first detailed molecular genetic study on the Galidiinae, a subfamily of the endemic Malagasy Eupleridae. Our results suggest the recognition of four species in the Galidiinae, rendering each genus monospecific, and not recognizing the recently described Galidictis grandidieri and Salanoia durrelli . Low levels of intraspecific divergence revealed some geographic structure for certain Galidiinae taxa, suggesting that environmental barriers have isolated certain populations in recent geological time. All taxa are forest dwelling and of urgent conservation concern associated with habitat degradation. Galidictis fasciata (top) and Salanoia concolor (bottom) (drawings by Velizar Simeonovski and previously published in Goodman2012 ).